A Closer Examination of Sexual Trauma During Deployment: Not all Sexual Traumas are Associated with Suicidal Ideation. Issue 1 (11th June 2015) - Monteith, Lindsey L.; Menefee, Deleene S.; Forster, Jeri E.; Bahraini, Nazanin H.
Abstract : Military personnel can be exposed to a wide range of sexual trauma while deployed, including sexual harassment and sexual assault. We examined whether different types of sexual trauma during deployment associated with recent suicidal ideation among previously deployed OEF/OIF/OND veterans admitted to trauma‐focused treatment ( n  = 199). More severe forms of sexual trauma (e.g., sexual assault) were significantly and positively associated with suicidal ideation. In contrast, sexual trauma involving verbal remarks (e.g., sexual harassment) was not associated with suicidal ideation. Our findings suggest that sexual harassment and sexual assault during deployment may be differentially associated with suicidal ideation.